The effect of mirror therapy on mental ill clients– Signs and symptoms Vishal Pawar - Pawar, Vishal (International Journal of Nursing Research, 2023)
Mirror therapy is a pioneering, non-invasive treatment for the treatment of mentally ill patients. The tool of this therapy is a mirror from which the patient receives visual feedback in order to train the brain to configure a new “body map.” This so-called map is simply the hard-wired mental representation that allows a person to be aware of where each component of the body is at all times, even in complete darkness. Aim: To assess the sign & symptoms of mentally ill clients before and after mirror therapy. Methods : Non-probability sampling and random method were used to select the samples from 60 mentally ill patients under treatment for mental illness from four Jagruti rehabilitation center, Yarawada mental hospital center, Nityanand rehabilitation center and Chaitanya rehabilitation center in Pune city Mirror therapy training was given to the patients in the rehabilitation centers. A pre-test was given to both groups. The self esteem scale (Rosenberg self esteem scale) used for the post-test was the same which was used for the pretest. Pilot study was conducted on 16 selected clients. Two groups were made, eight in experimental and eight in control group. Pre-testing was given to both the groups and mirror therapy was administered to experimental group. Post–test was given after 15 days. Results :In pre-test all 30 clients had low self esteem and in the post- test it became 0 samples showed low self esteem level whereas in the control group in the post test 30 samples showed low self esteem level and the same again show low self esteem because of no interventions in the control group. Thus it is concluded that the mirror therapy was effective in mentally ill clients. This also shows that mirror therapy has a significant effect on improvement of self-esteem level in the experimental group.